Survey on the Implementation of Preconception Care in Shanghai, China. Issue 6 (6th August 2015) - Ding, Yan; Li, Xiao‐Tian; Xie, Fei; Yang, Yu‐Lin
Abstract Background Recently, the Chinese government has promoted preconception care (PCC) to prevent birth defects. The objective of this study was to evaluate the implementation of PCC in Shanghai, China, following a 3‐year municipal project providing 'Free Pre‐pregnancy Health Evaluation Services' to 20 000 residents. Methods A retrospective questionnaire survey was undertaken among 12 309 pregnant women and 8997 of their partners during their initial prenatal visit in six hospitals with the most births in Shanghai. Results A total of 90% (n = 11 113) of the women and 87% (n = 7856) of the men were aware of PCC, and 40% (n = 4890) of the women and 35% (n = 3185) of the men had previously participated in PCC. Logistic regression showed that PCC participants were more likely to have a planned pregnancy, receive support from their partner for PCC services, were older, and have higher educational attainment and higher household incomes. Regardless of gender, there were significant differences between the participating and non‐participating groups in terms of prepregnancy changes in lifestyle and behaviour, such as folic acid supplementation, smoking cessation (for men only), avoiding passive smoking, abstaining from alcohol/drugs, and rubella/hepatitis B immunity. Conclusions The government‐led efforts proved to be effective in promoting PCC participation and positive lifestyle and behavioural changes in couples of childbearing age. Future efforts should target couples who are young, poorly educated, and/or from low‐income families. Strategies must ensure that the couples' knowledge of and positive attitudes toward PCC are translated into their practical participation in PCC.